2021
DOI: 10.3390/s21144814
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and Sensitive Inhibitor Screening Using Magnetically Modulated Biosensors

Abstract: Inhibitor screening is an important tool for drug development, especially during the COVID-19 pandemic. The most used in vitro inhibitor screening tool is an enzyme-linked immunosorbent assay (ELISA). However, ELISA-based inhibitor screening is time consuming and has a limited dynamic range. Using fluorescently and magnetically modulated biosensors (MMB), we developed a rapid and sensitive inhibitor screening tool. This study demonstrates its performance by screening small molecules and neutralizing antibodies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…The current techniques to identify protein–DNA interactions are usually time-consuming, expensive, or not sensitive enough. Recently, using an MMB platform, we demonstrated highly specific and sensitive detection of protein–protein interactions. , Here, we used the MMB platform to demonstrate, for the first time, a rapid and cost-effective approach to unambiguously detect protein–DNA interactions. The MMB-based protein–DNA assay was experimentally compared to EMSA, typically regarded as a gold standard for the detection of protein–DNA interactions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current techniques to identify protein–DNA interactions are usually time-consuming, expensive, or not sensitive enough. Recently, using an MMB platform, we demonstrated highly specific and sensitive detection of protein–protein interactions. , Here, we used the MMB platform to demonstrate, for the first time, a rapid and cost-effective approach to unambiguously detect protein–DNA interactions. The MMB-based protein–DNA assay was experimentally compared to EMSA, typically regarded as a gold standard for the detection of protein–DNA interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we introduced a novel method, termed magnetic modulation biosensing (MMB), which can rapidly detect interacting proteins, , antibodies, and specific nucleic acid sequences. , While the principles of the MMB technology have been described before, it has never been applied for detecting protein–DNA interactions. To detect protein–DNA interactions, two binding assays can be used.…”
mentioning
confidence: 99%
“…Roth, S. et al developed a rapid and sensitive inhibitor screening tool using fluorescence and magnetic modulated biosensor (MMBS) which could screen small molecules that inhibit the interaction between S1 and ACE2. The assay based on MMBS has high sensitivity, minimal non-specific binding, and was much faster than the commonly used ELISA [ 107 ]. Han, Y.X.…”
Section: Drug Screening Sensors Based On Ace2mentioning
confidence: 99%
“…Furthermore, if agent 33 does indeed show activity against SARS-CoV-2 at concentrations of 1.56-2.60 µM [88,89]), there are no published data confirming the activity of substance 32 against SARS-CoV-2. In addition, in [90] authors used fluorescent and magnetically modulated biosensors to develop a rapid and sensitive tool for screening inhibitors of S-protein and ACE2 interactions and showed that even at the highest concentration of compound 32 in 100 µM, inhibition of interaction of RBD of SARS-CoV-2 S-protein and ACE2 does not occur. The authors of [95] carried out high-throughput screening (HTS) of an extensive library of drugs that can be repurposed to find potential therapeutic agents against SARS-CoV-2.…”
Section: Binding Site In the Receptor-binding Domain Of Smentioning
confidence: 99%